Remains of Tefillin from Naḥal Ṣeʾelim (Wadi Seiyal) A Leather Case and Two Inscribed Fragments (34Se 1 A–B) - Adler, Yonatan 1976- (2017)
The present study presents and discusses the tefillin (phylactery) remains found in Cave 34 at Naḥal Ṣeʾelim within the framework of Yohanan Aharoni’s first 1960 expedition to the Judean Desert. Presented here are a leather tefillin case, never before reported upon, and two inscribed tefillin slips (34ṢePhyl A and 34ṢePhyl B) which have until now received only preliminary treatment. Very few close parallels to the Naḥal Ṣeʾelim tefillin slips are known from elsewhere in the Judean Desert. Both the tefillin slips and the case appear quite compatible with rabbinic descriptions and prescriptions, although there is little reason to label these ritual objects as in some way or another “rabbinic”. The paleographic analysis of the tefillin slips suggests that the texts were penned sometime in the second half of the first century ce. While a Bar Kokhba period date for the deposit of the tefillin remains in Cave 34 does not appear at all unlikely, an earlier dating—possibly First Revolt period—must not be precluded.
Keywords: Tefillin -- phylacteries -- Naḥal Ṣeʾelim -- Wadi Seiyal -- 34Ṣe Phylactery -- 34ṢePhyl